PENGEMBANGAN MEDIA PEMBELAJARAN PATUNGKABI (PAPAN HITUNG PERKALIAN PEMBAGIAN) BERBASIS CONTEXTUAL LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III SD N 11 SIPARMAHAN T.A 2023/2024 - Silalahi, Elsi K.; Irsan, Irsan (Universitas Negeri Medan, 2024)
The purpose of this research is to produce a valid and effective contextual learning-based Sculpture Learning Media (Division Multiplication Calculation Board) to improve the learning outcomes of class III students at SD N 11 Siparmahan. This research is a type of research and development using the ADDIE model. The subjects of this research were 19 students. The data collection techniques used are interviews, documentation, questionnaires and tests. Data analysis was carried out qualitatively and quantitatively. The media validity results obtained were 90% and declared valid, the practicality validation results obtained were 96%. The results of the media field trial were declared effective, as evidenced by the pretest and posttest results which increased from an average score of 48 to an average of 83.2.